2018
DOI: 10.1111/jcmm.14097
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified liposomes carrying TRAIL target activated hepatic stellate cells and ameliorate hepatic fibrosis in vitro and in vivo

Abstract: At present, no satisfactory anti‐liver fibrosis drugs have been used clinically due to the poor targeting ability and short half‐life period. This study aimed to explore the effects of a new TRAIL ( TNF ‐related apoptosis‐inducing ligand) preparation that can target aHSC s (activated hepatic stellate cells) on liver fibrosis and explain the possible underlying mechanism. Using our self‐made drug carrier pPB ‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Recently, it was found that resistance of myofibroblasts to apoptosis played a critical role in fibrotic diseases, and the induction of apoptosis in myofibroblasts could be an effective strategy to alleviate liver fibrosis (Hinz and Lagares 2020 ; Li et al 2019 , 2020 ; Oh et al 2016 ). In addition, Aghajanian et al ( 2019 ) reported that cardiac fibrosis could be alleviated through specific killing of activated cardiac fibroblasts by FAP-specific CAR T cells, indicating that specific killing of activated fibroblasts could also be an effective way to inhibit tissue fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that resistance of myofibroblasts to apoptosis played a critical role in fibrotic diseases, and the induction of apoptosis in myofibroblasts could be an effective strategy to alleviate liver fibrosis (Hinz and Lagares 2020 ; Li et al 2019 , 2020 ; Oh et al 2016 ). In addition, Aghajanian et al ( 2019 ) reported that cardiac fibrosis could be alleviated through specific killing of activated cardiac fibroblasts by FAP-specific CAR T cells, indicating that specific killing of activated fibroblasts could also be an effective way to inhibit tissue fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…To induce specific cell killing, besides inducing apoptosis by nanoparticle 35,36 or liposomes 28 and CAR-T cellmediated cell killing, ADCs are also a highly specific and effective strategy because of the high binding affinity and specificity of the antibody. 37,38 Generally speaking, ADC is composed of a monoclonal antibody tethered to a cytotoxic drug (known as the payload) via a chemical linker.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet-derived growth factor receptor beta (PDGFR-beta) on the surface of HSCs is recognized by the cyclic peptide known as the pPB, which may also recognize vitamin A. In a study, pPB-altered liposomes were used to convert recombinant human tumor necrosis factor-related cell apoptosis-inspired ligands to the HSC surface membrane, maintaining recombinant human-TNF-related apoptosis-inspired ligands circulation in living organisms and reducing fibrosis in both vitro and vivo [ 90 ]. Likewise, CXCR4 antagonist AMD3100 has the potential to attack HSCs.…”
Section: Role Of Nanotechnology In Liver Fibrosis Therapy Using Synth...mentioning
confidence: 99%